2017
DOI: 10.3390/ma10020215
|View full text |Cite
|
Sign up to set email alerts
|

Tensile and Flexural Properties of Cement Composites Reinforced with Flax Nonwoven Fabrics

Abstract: Abstract:The aim of this study is to develop a process to produce high-performance cement-based composites reinforced with flax nonwoven fabrics, analyzing the influence of the fabric structure-thickness and entanglement-on mechanical behavior under flexural and tensile loadings. For this purpose, composite with flax nonwoven fabrics with different thicknesses were first prepared and their cement infiltration was evaluated with backscattered electron (BSE) images. The nonwoven fabrics with the optimized thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 32 publications
4
28
0
3
Order By: Relevance
“…This phenomenon may be comparable with the failure mode of G3-type beam. The experimental results show that the concrete with nonwoven geotextile fabric was highly ductile in nature, as supported by the study of Claramunt et al [21]. This concrete's flexural strength and toughness could be more enhanced if an additional layer of nonwoven geotextile was used.…”
Section: Efficiency Of Strengthening Techniquesupporting
confidence: 68%
See 1 more Smart Citation
“…This phenomenon may be comparable with the failure mode of G3-type beam. The experimental results show that the concrete with nonwoven geotextile fabric was highly ductile in nature, as supported by the study of Claramunt et al [21]. This concrete's flexural strength and toughness could be more enhanced if an additional layer of nonwoven geotextile was used.…”
Section: Efficiency Of Strengthening Techniquesupporting
confidence: 68%
“…High deformability of polypropylene fibers may enhance this behavior. The deformability of this fabric is higher than 30% [21]. A 0-91% increase in ultimate load carrying capacity was found in the experiment, which depended on the arrangement of strengthened layers (Table 4).…”
Section: Behavior Of Rcb Under Bending Actionmentioning
confidence: 76%
“…Then, the layers were piled alternating the nonwoven direction (machine and cross direction) in a mold specially designed to apply a 3.5 MPa homogeneous pressure, pressure that was kept for 24 h. Then, the composites were cured in a humidity chamber (approximately 95% relative humidity, 20 � C) for 28 days. For further details, the procedure is described in previous papers [3,28].…”
Section: Production and Characterization Of Cement Compositesmentioning
confidence: 99%
“…In the literature, many studies have reported the measurement of mechanical and thermal properties of polymeric materials, including textile fabrics [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Darden and Schwartz proposed a framework to draw correlations between human sensory outcomes, such as smoothness and leather-like feel, and quantitative physical properties, such as friction coefficient and elastic modulus, for polymer fabrics [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…This method had the advantage of having an application in strain sensing and structural health monitoring by obtaining the electro-mechanical properties of the polymeric composite sensor. Claramunt et al developed a process to produce high-performance cement-based composites, reinforced with flax nonwoven fabrics, and took advantage of flexural and direct tension tests for analyzing the influence of the fabric structure—thickness and entanglement—on mechanical behavior [ 23 ]. These test methods and instruments helped with the development of the integration measurement of mechanical and dynamic heat transfer properties of porous polymeric materials.…”
Section: Introductionmentioning
confidence: 99%